A new species of Muhlenbergia (Poaceae, Chloridoideae, Cynodonteae) from the state of Guerrero, Mexico - Vigosa-Mercado, José Luis; Fonseca Juárez, Rosa María (Instituto de Ecología, A.C., 2019)
Background and Aims: Muhlenbergia is the most diverse genus of Poaceae in Mexico. During the development of the taxonomic study of the genus in Guerrero, herbarium material was found that could not be assigned to any known species. Therefore, it is proposed as a new species in this article.Methods: Herbarium material of the new species was examined and compared with specimens of Mexican species of Muhlenbergiadeposited in the collections CHAPA, ENCB, FCME, IEB, MEXU, UAGC and UAMIZ. Anatomy of the transversal section of the leaf blade and micromorphology of the lemma of the new species and M. watsoniana, which is the closest species, were observed.Key results: Muhlenbergia cristaliae is illustrated and described. This new species shares some morphological characteristics with species that possess uninervate glumes of the M. montana complex. Although the closest species is M. watsoniana, it differs with respect to the anatomy of the leaf blade and micromorphology of the lemma, among other macroscopic characteristics.Conclusions: Muhlenbergia cristaliae is considered endemic to Guerrero, without sufficient data to evaluate its conservation status for now.